The Impact of Direct-to-Patient Pharmaceutical Digital Marketing on Patient Outcomes in Diabetes Management: A Survey-Based Analysis of Patient Adherence - Ajvalia, Shrirang (Digital Repository of Theses, 2026)
In the US, the pharmaceutical industry is allowed to advertise prescription drugs directly to consumers through both traditional media and digital media outlets. These communications are intended to inform the consumer about their medications, promote safe and proper medication use to engage with their healthcare provider. This intention to assist consumers in making informed decisions and promoting appropriate use of medications creates a controversy on whether or not direct-to-patient (DTP) pharmaceutical marketing is to benefit patients or to simply serve as a means of increasing sales of the companies' products. Based on significant research, a patient benefit includes reminders to adhere to the medication’s protocol which improves their health outcomes. A cross-sectional survey was conducted to examine the relationship between DTP pharmaceutical social media marketing and adherence to prescribed diabetes medications in people with type 2 diabetes in order to ascertain if there is a positive patient benefit. The survey included 300 adults with type 2 diabetes who reside in the US and excluded those with type 1 diabetes (due to lack of lifestyle modification impact on the disease). In addition to assessing self-reported exposures to pharmaceutical digital marketing and self-reported medication adherence, the survey also assessed trust in pharmaceutical digital advertising, demographics and socioeconomic status, such as age, income and insurance status. Descriptive statistics and cross-tabulations were used to determine patterns in medication adherence related to financial status and insurance status in response to DTP pharmaceutical social media marketing exposures. Findings from the study indicate that increased levels of exposure to DTP pharmaceutical digital marketing are associated with increased self-reporting of medication adherence. Specifically, people who reported being exposed to DTP pharmaceutical digital marketing at least once per week had higher adherence rates than people who reported being exposed at least once every six months or less frequently. The results from the study indicate that differences in adherence were present based upon financial and insurance status; specifically, privately insured and higher-income participants exhibited higher adherence rates at all levels of marketing exposure, whereas lower-income and uninsured participants exhibited lower adherence rates at all levels of marketing exposure. Participants who reported lower levels of trust in pharmaceutical digital marketing exhibited weaker adherence patterns regardless of the amount of marketing exposure they reported receiving. Overall, findings from the current study suggest that DTP pharmaceutical digital marketing can function as an engagement mechanism to support medication adherence in people with diabetes if they have adequate access to care, however, it is less effective in overcoming financial and structural barriers to accessing treatments.